Converting Waste into Treasure: Efficient Adsorption of Cr(VI) Using Iron-Modified Rice Straw Biochar - Hang Liu; Runlin Yao; Mingling Yu; Zongda Ye; Yingrui Lu; Xiaolong Yu; Jin Tang; Jianteng Sun (Toxics)
Hexavalent chromium (Cr(VI)) is of significant interest in the environmental field due to its high toxicity. Biochar is commonly used as an adsorbent for Cr(VI) removal from wastewater. However, its lower removal efficiency remains a persistent challenge. This study develops an iron-modified rice straw biochar through a simple precipitation and pyrolysis method and applies it for Cr(VI) removal in wastewater, which could convert waste into treasure and improve the adsorption performance of adsorbent. In the adsorption experiments, the results revealed that the adsorption efficiency of Cr(VI) reached 95.54% within 480 min (conditions: adsorbent dosage 2.67 g/L, pH 2.5, temperature 25 ± 2 °C). The Langmuir isotherm model was more suitable to describe the adsorption behavior of Cr(VI) by Fe-BC, and the fitted adsorption capacity achieved 10.03 mg/g. The experimental process was better described by the pseudo-second-order kinetic model, indicating that the adsorption process chemical adsorption was the rate-limiting step. The thermodynamic experiments revealed that the adsorption process of Cr(VI) by Fe-BC was spontaneous and endothermic. Column experiments demonstrated that a lower flow speed was beneficial to adsorption performance. Mechanistic studies highlighted the synergistic roles of electrostatic attraction, ion exchange, and reduction in Cr(VI) removal. These findings provide novel perspectives and innovative approaches for the development and application of adsorbents.